Stem Cells for Bone Regeneration: From Cell-Based Therapies to Decellularised Engineered Extracellular Matrices - James N. Fisher; Giuseppe M. Peretti; Celeste Scotti (Hindawi Limited, 2016)
Currently, autologous bone grafting represents the clinical gold standard in orthopaedic surgery. In certain cases, however, alternative techniques are required. The clinical utility of stem and stromal cells has been demonstrated for the repair and regeneration of craniomaxillofacial and long bone defects although clinical adoption of bone tissue engineering protocols has been very limited. Initial tissue engineering studies focused on the bone marrow as a source of cells for bone regeneration, and while a number of promising results continue to emerge, limitations to this technique have prompted the exploration of alternative cell sources, including adipose and muscle tissue. In this review paper we discuss the advantages and disadvantages of cell sources with a focus on adipose tissue and the bone marrow. Additionally, we highlight the relatively recent paradigm of developmental engineering, which promotes the recapitulation of naturally occurring developmental processes to allow the implant to optimally respond to endogenous cues. Finally we examine efforts to apply lessons from studies into different cell sources and developmental approaches to stimulate bone growth by use of decellularised hypertrophic cartilage templates.